Evaluation of the performance of contemporary shipbuilding industries in Bangladesh - Zakaria, N.M. Golam; Iqbal, K. Shahriar; Hossain, K. Akhter (Journal of Naval Architecture and Marine Engineering, 2011)
In this paper, an effort has been made to evaluate the present shipbuilding industries in Bangladesh. To do this, at first an overall picture of this industries have been depicted by identifying the actual shipbuilding practice in both public and private sector. Relevant data have been explored through extensive review of literature, field visits, interacting with shipyard and Ship owners, shipyard managers, Government regulatory and monitoring bodies using structured, unstructured and open ended questionnaires. Existing and upcoming yards have been identified and yards have been categorized by describing the shipyard in terms of modern shipbuilding requirements. The labor cost, labor hour, relative labor rate, productivity etc. have been quantified and compared with other nations. An investigation of cost breakdown of a sample exportable quality ship has been assessed to find out percentage of local components of total cost structure. The potentiality, capability and problems of the shipbuilding sector of Bangladesh have been identified & some recommendations have been made in line with this study. DOI: 10.3329/jname.v7i2.5407